2010
DOI: 10.1007/s10681-010-0257-1
|View full text |Cite
|
Sign up to set email alerts
|

Realized gains from selection for spring wheat grain yield are different in conventional and organically managed systems

Abstract: Breeding spring wheat (Triticum aestivum L.) specifically for organic production has been suggested by producers and researchers alike. To investigate the effects of management systems on selected spring wheat breeding line performance in multi-location tests in the northern Great Plains, we used a randomly derived population of 79 F6-derived recombinant inbred lines (RILs) from a cross between the Canadian hard red spring wheat cultivar AC Barrie and the CIMMYT derived cultivar Attila. The population, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 24 publications
2
42
0
Order By: Relevance
“…Organic production systems are typically, though not always, different from conventional systems in soil nutrient status (E and M), fertility inputs (M), resilience to drought conditions (E and M), nitrogen mineralization rate (E and M), and timing of key operations such as planting date (M) [4,5]. Hence it is expected that the same genotypes in an organic and conventional cropping system will have different phenotypes even when grown under identical climatic or weather conditions, which has been confirmed by previous research [4,6,7].…”
Section: Introductionmentioning
confidence: 57%
“…Organic production systems are typically, though not always, different from conventional systems in soil nutrient status (E and M), fertility inputs (M), resilience to drought conditions (E and M), nitrogen mineralization rate (E and M), and timing of key operations such as planting date (M) [4,5]. Hence it is expected that the same genotypes in an organic and conventional cropping system will have different phenotypes even when grown under identical climatic or weather conditions, which has been confirmed by previous research [4,6,7].…”
Section: Introductionmentioning
confidence: 57%
“…This experiment was conducted under conventional agronomic practices, and the results are applicable to both farming systems. However, as has been shown in previous studies, genotype by environment interactions can cause rank changes to occur in the performance of cultivars between conventional and organic systems [28,29]. While this study suggests inbred parents that have the potential to adapt to higher planting densities, lines identified for organic farming systems should be tested under organic conditions to evaluate their performance in the environment of intended use.…”
Section: Discussionmentioning
confidence: 74%
“…Breeders in both Manitoba and Alberta have found that spring wheat (Triticum aestivum L.) lines selected under organic management outyielded conventionally selected lines when all were grown under organic management, and concluded that targeted crop breeding programmes for organic varieties would be beneficial (Reid et al 2011;Kirk et al 2012). Similar effects have been observed in other crops such as lentil (Lens culinaris Medik.…”
Section: Crop Varieties and Genetic Diversitymentioning
confidence: 91%